2022
DOI: 10.3390/cells11203316
|View full text |Cite
|
Sign up to set email alerts
|

Low Nephron Number Induced by Maternal Protein Restriction Is Prevented by Nicotinamide Riboside Supplementation Depending on Sirtuin 3 Activation

Abstract: A reduced nephron number at birth, due to critical gestational conditions, including maternal malnutrition, is associated with the risk of developing hypertension and chronic kidney disease in adulthood. No interventions are currently available to augment nephron number. We have recently shown that sirtuin 3 (SIRT3) has an important role in dictating proper nephron endowment. The present study explored whether SIRT3 stimulation, by means of supplementation with nicotinamide riboside (NR), a precursor of the SI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Several studies have highlighted the role of Sirt3 in protecting from oxidative damage by its deacetylating activity of mitochondrial enzymes resulting in the regulation of ROS production and clearance [ 27 ]. Dikalova and colleagues showed that SIRT3 dictates vascular dysfunction by regulating oxidative stress via SOD2 [ 41 ], a direct target of SIRT3 deacetylase activity in the adult kidney [ 42 , 43 ]. In our setting, increased acetylation levels of SOD2 were found in Sirt3 -deficient mice, thus implying decreased anti-oxidant capacity of the kidney and further increased oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have highlighted the role of Sirt3 in protecting from oxidative damage by its deacetylating activity of mitochondrial enzymes resulting in the regulation of ROS production and clearance [ 27 ]. Dikalova and colleagues showed that SIRT3 dictates vascular dysfunction by regulating oxidative stress via SOD2 [ 41 ], a direct target of SIRT3 deacetylase activity in the adult kidney [ 42 , 43 ]. In our setting, increased acetylation levels of SOD2 were found in Sirt3 -deficient mice, thus implying decreased anti-oxidant capacity of the kidney and further increased oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…NR supplementation proved beneficial in AKI with ischaemia‒reperfusion injury, as evidenced by a slowing increase of serum urea nitrogen and creatinine levels and tubular damage [ 186 ]. Restoration of Sirt3 activity, restoration of reduced glomerular numbers, improvement of glomerular podocyte density, and sparse density of renal capillaries by administration of NR supplementation to mothers on a low-protein diet provides a therapeutic option to potentially limit the long-term sequelae of a reduced kidney number in adulthood [ 183 ]. Intracellular NAMPT is a critical enzyme in the NAD + remediation synthesis pathway.…”
Section: Sirtuin Regulatorsmentioning
confidence: 99%
“…NAD + supplementation, by oral administration of NAM, NA, NR, dihydronicotinamide riboside (reduced NR, NRH) and NMN, and SIRT activation may be useful in the prophylaxis and treatment of AKI, if some recent studies on MT metabolism are developed [ 109 , 110 , 111 , 112 , 113 ]. For example, in an experimental model of newborn (one day) mice from mothers fed a low protein diet, NRS restored the SIRT3 expression, by the induction of PGC-1α, improved MT and cellular protection against OXS, increasing the density of nephrons, renal capillaries, and glomerular podocytes [ 114 ].…”
Section: Effects Of Nicotinamide Riboside On Several Organs and Systemsmentioning
confidence: 99%